2002
DOI: 10.1021/bi0160720
|View full text |Cite
|
Sign up to set email alerts
|

l-Phenylalanine Binding and Domain Organization in Human Phenylalanine Hydroxylase:  A Differential Scanning Calorimetry Study

Abstract: Human phenylalanine hydroxylase (hPAH) is a tetrameric enzyme that catalyzes the hydroxylation of L-phenylalanine (L-Phe) to L-tyrosine; a dysfunction of this enzyme causes phenylketonuria. Each subunit in hPAH contains an N-terminal regulatory domain (Ser2-Ser110), a catalytic domain (Asp112-Arg410), and an oligomerization domain (Ser411-Lys452) including dimerization and tetramerization motifs. Two partially overlapping transitions are seen in differential scanning calorimetry (DSC) thermograms for wild-type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
93
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(103 citation statements)
references
References 50 publications
9
93
1
Order By: Relevance
“…Similar results demonstrating resolved transitions for separate structural domains have been noted for the thermal unfolding of phenylalanine hydroxylase, which were attributed to the unfolding of the N-terminal regulatory domain, followed by unfolding of the rest of the enzyme (43). The C-terminal helix region of GSTA1-1 is likewise known to behave in an independent manner compared with the remainder of the protein, and it is likely that the low temperature transition in the DSC thermogram of GSTA1-1 corresponds to changes in this element.…”
Section: Resultssupporting
confidence: 76%
“…Similar results demonstrating resolved transitions for separate structural domains have been noted for the thermal unfolding of phenylalanine hydroxylase, which were attributed to the unfolding of the N-terminal regulatory domain, followed by unfolding of the rest of the enzyme (43). The C-terminal helix region of GSTA1-1 is likewise known to behave in an independent manner compared with the remainder of the protein, and it is likely that the low temperature transition in the DSC thermogram of GSTA1-1 corresponds to changes in this element.…”
Section: Resultssupporting
confidence: 76%
“…3). The observed effect of L-Phe binding on the biphasic thermal denaturation profile of wthPAH (37) (Fig. 3) further supports the interpretation of the SPR response in terms of a biphasic time course, possibly contributed by the two domains (8).…”
Section: Hinge-bending Region In the Regulatory Domain That Controls supporting
confidence: 78%
“…3). Previous thermal denaturation studies by differential scanning calorimetry and far-UV CD spectroscopy on the wild-type and truncated forms of hPAH (37) have suggested that the thermodynamically irreversible denaturation of the full-length wild-type tetramer occurs through a sequential unfolding of the N-terminal regulatory domains (T m ϳ46°C) and the catalytic domains (T m ϳ54°C) (37). Both transitions are shifted to higher temperatures in the presence of L-Phe (37) (Fig.…”
Section: Hinge-bending Region In the Regulatory Domain That Controls mentioning
confidence: 96%
“…Generally, an increase in the scan rate leads to an increase in the transition temperature up to a so-called high scan limit, where the irreversible step does not affect the hot side of the thermal peak. At this limit, the transition temperature versus the scan rate reaches a plateau (41). Due to the intrinsic limitation of the scan rates used in DSC, the plateau was experimentally unachievable in our measurements (Fig.…”
Section: Figmentioning
confidence: 83%